2005
DOI: 10.1086/432377
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Genomewide Linkage Scan of 1,233 Families for Prostate Cancer–Susceptibility Genes Conducted by the International Consortium for Prostate Cancer Genetics

Abstract: Evidence of the existence of major prostate cancer (PC)-susceptibility genes has been provided by multiple segregation analyses. Although genomewide screens have been performed in over a dozen independent studies, few chromosomal regions have been consistently identified as regions of interest. One of the major difficulties is genetic heterogeneity, possibly due to multiple, incompletely penetrant PC-susceptibility genes. In this study, we explored two approaches to overcome this difficulty, in an analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
92
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 28 publications
10
92
0
1
Order By: Relevance
“…The International Consortium for Prostate Cancer Genetics (ICPCG), which seeks to improve the mapping of PCa genes, has emphasized that one of the major difficulties in studying PCa is genetic heterogeneity, possibly due to multiple, incompletely penetrant PCasusceptibility genes . Indeed using parametric (dominant and recessive) and nonparametric analyses on 1,233 families, Xu et al (2005) identified five distinct chromosomal regions with "suggestive" linkage (LOD score >1.86) to PCa, namely 5q12, 8p21, 15q11, 17q21, and 22q12. Subsets of the analyzed group of families characterized by large numbers of early-onset (≤65 years) PCa, which are more likely to segregate highly penetrant mutations, provided stronger evidence of linkage in several regions (including the 22q12 locus, with a LOD score of 3.57).…”
Section: Introductionmentioning
confidence: 99%
“…The International Consortium for Prostate Cancer Genetics (ICPCG), which seeks to improve the mapping of PCa genes, has emphasized that one of the major difficulties in studying PCa is genetic heterogeneity, possibly due to multiple, incompletely penetrant PCasusceptibility genes . Indeed using parametric (dominant and recessive) and nonparametric analyses on 1,233 families, Xu et al (2005) identified five distinct chromosomal regions with "suggestive" linkage (LOD score >1.86) to PCa, namely 5q12, 8p21, 15q11, 17q21, and 22q12. Subsets of the analyzed group of families characterized by large numbers of early-onset (≤65 years) PCa, which are more likely to segregate highly penetrant mutations, provided stronger evidence of linkage in several regions (including the 22q12 locus, with a LOD score of 3.57).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, FTC may more closely resemble familial prostate cancer where there is a demonstrated interest in genetic testing, [17][18][19][20] with numerous candidate susceptibility loci having been identified, but to date no major susceptibility genes have been discovered to account for the majority of familial cases. 21 Thus, it is likely to take longer than anticipated to identify an FTC susceptibility gene and acquire the ability to perform germline mutation testing than it did with Hereditary Breast Ovarian Cancer (HBOC) or Hereditary Non Polyposis Colorectal Cancer (HNPCC). Even if a susceptibility gene were discovered tomorrow, it would probably take six months or more to get a clinical test to market; thus, our question about interest in a hypothetical genetic test was framed in a six-month context.…”
mentioning
confidence: 99%
“…1 Familial aggregation of the disease indicates that it has a genetic component. 2,3 Evidence presented by the International Consortium for Prostate Cancer Genetics (ICPCG) 4 highlighted five suggestive linkage regions supporting putative susceptibility loci reported earlier, including one on chromosome 5q. 5 More recently, several genome-wide association studies (GWAS) in large independent casecontrol data sets have provided compelling evidence for multiple new susceptibility loci.…”
Section: Introductionmentioning
confidence: 58%